Lifestyle or pharmacotherapy in cardio-metabolic disease prevention - Borenyi S. Seidu; Hanad Osman; Samuel Seidu (Therapeutic Advances in Cardiovascular Disease, 2023)
Cardio-metabolic diseases are the leading causes of premature death worldwide. The conditions are together some of the most prevalent and severe multimorbidities and include conditions such as diabetes, hypertension, coronary heart disease and stroke. People with these conditions are at a higher risk of all-cause death and have a reduction in life expectancy when compared to patients without cardio-metabolic disorders. As a result of the increasing prevalence and impact of cardio-metabolic multimorbidity on disability, no healthcare system can ‘treat’ its way out of this pandemic. ‘Treating our way out’ requires the use of multiple medications which can lead to improper prescribing, insufficient compliance, overdosing or underdosing, improper drug choice, insufficient monitoring, unfavourable drug effects, and drug interactions and inappropriate wastes and costs. Therefore, individuals living with these conditions should be empowered to adopt lifestyle changes that foster independent living with their conditions. Adopting these healthy lifestyles such as smoking cessation, improving dietary habits, sleep hygiene and physical activity is a suitable adjunctive measure if not an alternative to polypharmacy in cardio-metabolic multimorbidity.